Pengembangan Aplikasi E-Commerce Anggrek berbasis Android menggunakan Clean Architecture (Studi Kasus: PT. Java Indo Arjuna) - Aransa Fitra Prawira; Widhy Hayuhardhika Nugraha Putra; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
E-Commerce is the application of technology that is often used and is growing rapidly to date, this is because it facilitates the process of buying and selling goods between sellers and buyers can be done anywhere and anytime. Supported by the spread of the COVID-19 virus, the community is forced to comply with government regulations, namely the implementation of community activity restrictions (PPKM) so that offline buying and selling activities are difficult to carry out. PT Java Indo Arjuna (JAVINA) is a company buying and selling orchid plants and their equipment which has also been affected by COVID-19. At first, Javina carried out buying and selling activities with consumers using WhatsApp social media. Due to the increasing number of customers during the pandemic, the services provided via WhatsApp were not handled properly, Javina needed to reply one by one, from product-related info to confirming payments. This research was conducted to build an Android-based Orchid E-Commerce Application using Clean Architecture. The application is developed on the android platform. IsiTaman application is built using the Scrum method. This method was chosen because the initial requirements are still few, it can increase or change during development. IsiTaman testing is done by testing Blackbox and usability. Blackbox testing resulted in a 100% system success rate. In usability testing, the application has a System Usability Scale (SUS) value of 81.4. This value makes this application classified as acceptable category.